Finance; Education; Management; RKAS. - Marwa, Dini Nuraeni; Prastiwi, Ari; Wasol, Wasol (Journal of Management Review, 2024)
This research is motivated by the Covid 19 pandemic which has changed the system order in the world, especially in the education sector. Finance is one of the resources that directly support the effectiveness and efficiency of education management. Especially during the Covid-19 pandemic, this is a big challenge for school institutions in managing education finances so that the availability of funds is managed optimally. The purpose of this study was to determine the implementation of educational financial management in the process of planning, implementing, and monitoring during the Covid-19 pandemic at SMP Negeri 2 Jeruklegi. This study uses a qualitative descriptive approach by examining the facts that occurred. The research was conducted at SMP Negeri 2 Jeruklegi Cilacap. The data collection technique used was interviews sourced from the school committee, the principal, and the treasurer of the SMP Negeri 2 Jeruklegi school. Financing management at SMP Negeri 2 Jeruklegi includes planning, implementation and supervision, focusing on the needs of schools, teachers and students. The implementation of educational financial management at SMP Negeri 2 Jeruklegi went well according to procedures and directions, so that plans and realizations were appropriate. Because currently it is still in the pandemic period so that the budget for facilities and infrastructure as well as in financing standards has a large enough budget, because there is something that must be budgeted for handling the impact of the Covid-19 disaster.